Time to get ready: conceptualizing the temporal and spatial dynamics of formative phases for energy technologies - Bento, N.; Wilson, C.; Anadon, L. D. (Energy Policy, 2018)
Implementing the Paris agreement to prevent dangerous climate change requires energy system transformation and rapid diffusion of low-carbon innovations. In this paper we investigate both the temporal and spatial dynamics of formative phases by which energy technologies prepare for growth. Drawing on a review of diverse literatures, we offer a definition of the formative phase which clarifies its scope and duration, and identifies its main technological and economic determinants. We use parametric hazard models to assess the relative strengths of these determinants on formative phase durations for a sample of 15 energy technologies diffusing over time in their respective initial markets. We find that substitutability has stronger effects in accelerating the end of formative phases than installed capacity and prices. We extend our analysis using nonparametric models to analyze the spatial diffusion of formative phase durations from initial to follower markets. We find that formative phase durations are long outside initial markets as well, showing only signs of acceleration in latecomer regions. Our results imply risks for policies trying to accelerate the diffusion of large innovations without ready markets in both initial and follower markets.